Various Parameters Influencing To Ambarella (Spondias Dulcis) Jam Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Ambarella (Spondias dulcis) has a strong radical scavenge and can be considered as good source of natural antioxidants. Ambarella fruit has a sweet sour taste. The ambarella fruit can be eaten directly in fresh or processed into wine, syrup, nectar, etc. Our attempts to process it into jam were investigated. We focused on investigation of blanching (time, temperature); sugar soaking (time of soaking, sugar addition); evaporation (pectin ratio and time of boiling); preservation (temperature, way of packing) during ambarella jam production. Our results demonstrated that blanching ambarella fruit at 90 oC at 45 seconds was enough to inactivate enzymes; soaking ambarella fruit with 30 % sugar in 15 minutes was enough to get the optimal sensory characteristic of ambarella juice; boiling in 25 minutes with 0.15% pectin was enough to get the optimal total soluble solid (> 65 oBrix) of ambarella jam; ambarella jam should be kept in 4 oC by vaccum packing bag.Keywords: Ambarella, Jam, Blanching, Pectin, Soaking, Preservation